Telecomm Subscriber Management System(TSMS) - HASSAN, CHIMA ISMAEL (Universiti Teknologi Petronas, 2013)
In the current fast growing rate of mobile phone users, Telecomm Subscriber Management System (TSMS) leads to a good management of subscribers’ number by indicating the most current status of a subscriber number in telecommunication world. It helps to improve the management of subscriber numbers efficiently and also it helps to increase the revenue generated event (RGE) by the subscriber where lies the goals and objectives of any mobile telecommunication operators. This work is an automation of manual processes whereby we validate data first to ensure that there is no redundant data then we proceed to the subscriber classification. In Parallel there are several concerns that this project will provide an efficient improvement of subscriber number management that helps the telecommunication company to make significant profit in order to ensure its success in the market. There are problems are : inefficient subscriber’s number management which is leading to difficulties in identifying subscriber number’s status as well difficulties to clarify the usage of the block that have owned the company. There are several research papers that have been discussed about this. This work is a significant enhancement of resealed methods procedures of the researches and studies done previously. The implementation of this system will help the company in keeping the database updated, will reduce missing data and data redundancy as well as data inconsistency and unreliable data in the database as well as it has great advantages in their profit margin improvement.